The Effect of Slag Optical Basicity on Alloying Element Losses of Steel by Electroslag Remelting (ESR) - Birol, Burak; Saridede, Muhlis Nezihi (SPRINGER INDIA, 2016)
Slag properties affect the efficiency of Electro Slag Remelting (ESR) process by removing the quality impairing elements (S, P, etc.), while avoiding valuable alloying element losses. Therefore, a relation between element losses and optical basicity of slags, which may be assumed to be an enhanced approach to basicity concept, would play a crucial role on predicting and selecting the optimum slag composition for ESR process. The primary contribution of this paper is to investigate the effect of optical basicity of various slags on the composition change of high sulphur containing AISI 12L14 (DIN11SMnPb37) free-cutting and AISI M2 (DIN HS6-5-2C) high speed steels. For this purpose steel bars were remelted under different slag compositions at constant melting conditions. According to the chemical analysis of the products, it was observed that the element losses increase related to increasing optical basicity of slags. On the other hand, these alloying element changes show variety on steel types. High speed steel shows a relatively low alloying element changes due to its high carbide content, while higher losses were discovered in free cutting steels.
Keywords: ESR; Slag; Element losses; Optical basicity; AISI 12L14; AISI M2; SULFIDE CAPACITY; LIQUID-IRON; DEPHOSPHORIZATION; PHOSPHATE; Metallurgy & Metallurgical Engineering